2014
DOI: 10.1159/000355807
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association Between Bone-Specific Alkaline Phosphatase and Vascular Calcification of the Hand Arteries in Male Hemodialysis Patients

Abstract: Background/Aims: Bone-specific alkaline phosphatase (BAP) hydrolyzes pyrophosphate, which inhibits vascular calcification. We examined association between serum BAP and vascular calcification of male hemodialysis patients. Methods: Hand roentgenography of 167 male maintenance hemodialysis patients was conducted, and visible vascular calcification of the hand arteries was evaluated. Serum levels of 3 bone formation markers (BAP, osteocalcin, and N-terminal propeptide of type I collagen) and 2 bone resorption ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In the prior study, bone-specific ALP was demonstrated to be associated with bone turn-over following renal transplantation [22]. Moreover, higher serum bone-specific ALP was reported to be associated with the presence of vascular calcification in male HD patients [23]. However, we did not examine the relationship of bone-specific ALP levels and mortality in HD patients in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…In the prior study, bone-specific ALP was demonstrated to be associated with bone turn-over following renal transplantation [22]. Moreover, higher serum bone-specific ALP was reported to be associated with the presence of vascular calcification in male HD patients [23]. However, we did not examine the relationship of bone-specific ALP levels and mortality in HD patients in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…Of the 46 studies included in this review, 26 (56%) were designed specifically to examine the relationship between OC and markers of calcification or atherosclerosis (20, 22, 2427, 2947). The other 20 studies evaluated OC among a number of measurements, as a covariate, or in secondary analyses (21, 23, 28, 4861). Forty-four out of the 46 studies were cross-sectional in design.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where no response from authors was obtained ( n  = 8), they could not be included in the statistical analysis (2027). One author declined to supply requested information (28). Studies were weighted by sample size, and statistical significance was set at p  < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Only bone-specific alkaline phosphatase is statistically significantly higher in patients with vascular calcifications than in the other patients (p<0.05). Multi-variance analysis demonstrated a statistically reliable association (p<0.0001) between the bone-specific alkaline phosphatase logarithm on the one hand and the calcification of the vessels (15).…”
Section: Methodsmentioning
confidence: 89%